2018
DOI: 10.1186/s12931-018-0733-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum IgG subclass levels and risk of exacerbations and hospitalizations in patients with COPD

Abstract: BackgroundThe literature is scarce regarding the prevalence and clinical impact of IgG subclass deficiency in COPD. We investigated the prevalence of IgG subclass deficiencies and their association with exacerbations and hospitalizations using subjects from two COPD cohorts.MethodsWe measured IgG subclass levels using immunonephelometry in serum samples from participants enrolled in two previous COPD trials: Macrolide Azithromycin for Prevention of Exacerbations of COPD (MACRO; n = 976) and Simvastatin for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…In this context, others have shown that about 25% of COPD patients have total serum IgG levels below the lower limit of normal, consistent with our findings in smokers without COPD. This is associated with an increased incidence of exacerbations and hospitalizations (usually because of respiratory tract infections), and this is mainly in patients with deficiencies in IgG1 and/or IgG2 subclasses . This is consistent with reports that intra‐venous Ig (IVIG) replacement therapy reduces respiratory infections and exacerbations in COPD .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this context, others have shown that about 25% of COPD patients have total serum IgG levels below the lower limit of normal, consistent with our findings in smokers without COPD. This is associated with an increased incidence of exacerbations and hospitalizations (usually because of respiratory tract infections), and this is mainly in patients with deficiencies in IgG1 and/or IgG2 subclasses . This is consistent with reports that intra‐venous Ig (IVIG) replacement therapy reduces respiratory infections and exacerbations in COPD .…”
Section: Discussionsupporting
confidence: 88%
“…Thus, there is a strong consensus of evidence that smoking is associated with reduced IgG levels both systemically and in the oral mucosa. It would be of interest to examine the effects of smoking on IgG subclasses, especially as these are known to be affected in COPD …”
Section: Discussionmentioning
confidence: 99%
“…Its role has been evaluated mostly in children, and IgG2 deficiency has been reported to be an important cause of recurrent sinopulmonary infections and otitis caused by those pathogens . For adults, the Canadian Respiratory Research Network recently reported that low levels of IgG subclasses such as IgG1 and IgG2 were risk factors for exacerbations and/or hospitalizations in patients with chronic obstructive pulmonary disease . Therefore, it is plausible that a low IgG2 level could be associated with susceptibility to bacterial infection not only in children but also in adults, especially those with underlying diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they revealed that approximately 1 in 5 COPD patients had one or more IgG subclass deficiencies and reduced IgG1 or IgG2 levels were associated with increased risk of AECOPD, but only IgG2 remained as an independent predictor of hospitalisations. Lower IgG1 and IgG2 levels were detected in patients who developed two or more exacerbations during follow‐up …”
Section: Biomarkersmentioning
confidence: 99%
“…Only a few articles have described the association between the IgG subclass deficiencies and COPD exacerbation risk . Using samples from two large COPD trials, Leitao Filho et al found that reduced total IgG levels are associated with increased risk of AECOPD and hospitalisations, with the greatest risk observed among participants with total IgG levels <7.0 g/L .…”
Section: Biomarkersmentioning
confidence: 99%